The Role of the Decrees of Peter the Great in the Formation and Development of Russian Pharmacy. Part 2 - K. S. Guzev (Разработка и регистрация лекарственных средств)
The second part of the article presents the next steps of Peter the Great to improve the functioning of the pharmacy service in Russia. To improve the management of the nascent pharmacy service, the Emperor established the Main Pharmacy in the Pharmaceutical Prikaz (i.e. chamber) and appointed its head, endowed with clearly defined rights and responsibilities. The development of the pharmacy service in Russia was facilitated by the organization of hospitals, in which pharmacies were established. Usually, foreigners worked there, but they shared their pharmaceutical knowledge with young people of different social strata. At the same time, Peter the Great stimulated the emergence of chemical industries, issuing letters of commendation to Russian entrepreneurs to open chemical industries. To ensure the maintenance and financial sustainability of hospitals and pharmacies the Emperor issues a decree on a new tax (one kopeck from each ruble) for all military and civilian service people. Peter the Great paid special attention to the training of local people as personnel. So, at first, he invited specialists from abroad, but later, he constantly sent all young people to study literacy, arithmetic and geometry in schools by his Decrees. The most talented children of nobles, boyars and merchants were sent to study abroad. In the last year of his life, Peter the Great established the Academy of Sciences, which, according to his plans, should include the University, where medical and pharmaceutical sciences would be studied at the Faculty of Medicine. Thus, Peter the Great consistently and systematically formed the main directions of the domestic pharmacy service, which, while developing harmoniously, was supposed to ensure civil health.